Business Feasibility Study in the Planning of Bhayangkara Hospital Development in Labuan Bajo 2024 - Suputra, Gde Yoga Ari; Aziz, Abdul; Supardjo, Supardjo (International Journal of Business, Law, and Education, 2025)
The Indonesian National Police plans to construct Bhayangkara Hospital Labuan Bajo to address the shortage of hospital beds in West Manggarai, which still requires 85 beds based on WHO standards. This study employs a qualitative descriptive-analytic approach, utilizing participatory observation, in-depth interviews, FGDs, and secondary data analysis. Findings indicate that the hospital's construction is feasible due to existing market demand, particularly for emergency services like sea ambulances and hyperbaric treatment. The development plan meets technical standards, and financial analysis using NPV, IRR, and Payback Period confirms its viability and long-term profitability. The project is expected to enhance healthcare services for both residents and tourists while supporting Labuan Bajo’s tourism and healthcare sectors.